The Influence of Psychological Empowerment and Self-Compassion on Resilience in Women with Dual Roles - Weliangan, Hally; Ardradhika , Alif Naafi; Huda, Nurul (Kuras Institute, 2024)
Women with dual roles face various challenges every day in their lives. Managing a husband and children, while also choosing to work, means that these women must balance their time between their roles as mothers and wives. The challenges faced by mothers with dual roles require resilience. Factors that influence resilience include psychological empowerment and self-compassion. The aim of this study is to examine the influence of psychological empowerment and self-compassion on resilience in women with dual roles. The results of the study show that the hypothesis is accepted; there is a simultaneous influence of empowerment and self-compassion on resilience in women with dual roles. The implications of this study suggest the need for resilience education for every woman with dual roles so that they can become resilient and capable of overcoming personal and family problems, as well as challenges at work, thereby achieving well-being in their roles.